Analysis of Factors that Influence the Acceptance of Using Online Retail Applications: A Case Study of XYZ Wholesale and Retail Stores - Inayah, Suci -; Sensuse, Dana Indra; Lusa, Sofian (Jurnal Sisfokom (Sistem Informasi dan Komputer), 2024)
E-commerce users in Indonesia continue to increase along with advances in digitalization. This causes a trend to occur where many offline shop entrepreneurs are responding to changes in consumer behavior by creating online shopping applications to maintain the existence of their business to be consistent with time progress. The purpose of this research is to find out what factors affect user acceptance of online retail applications used for online shopping at XYZ stores using the UTAUT2 acceptance model. In line with changes, case studies were conducted on grocery stores and retail stores that carried out digital innovation by creating online retail applications for their consumers. The research was conducted using a mixed method, data was collected through interviews with sources and using a questionnaire spread to 149 research sample consumers. The data processing technique uses PLS-SEM with SmartPLS tools. The research results show that 4 factors influence the use of online retail applications, including hedonic motivation, habit, behavioral intention, and application use. The results of this research can be used as material for management considerations to increase the excellence of the application so that user interest in online shopping using the application at XYZ store increases